Bitstream radar waveforms for generic single-chip radar. Issue 6 (22nd August 2017) - Bjørndal, Øystein; Hamran, Svein-Erik; Lande, Tor Sverre
Abstract : Bitstreams, square wave digital signals, enable flexible radar implementations in modern digital technology. By using bitstreams in place of analog sinusoidal waveforms, we can realize continuous-wave (CW), stepped-frequency CW, frequency-modulated CW, or even pseudo random noise-sequence and pulsed radars, all with a single bit of amplitude resolution. The building blocks are a programable waveform generator, a sweep threshold quantizer, digital delay, and a digital XOR gate as a mixer. This gives us a novel, almost fully digital (requiring only a comparator) system, as previously proposed and which is extended here. The flexibility of the transmitter allows for easy switching between waveforms and the bitstream signal can be processed with single-bit digital gates. Single-bit signals allows for exploration of novel continuous time non-clocked digital implementations to maximize speed and energy efficiency. Mixing frequencies with a digital XOR gate creates harmonics, which are explored for multiple solutions utilizing digital delay. Analytical as well as simulation results are presented. Initial measurements from a 90 nm CMOS chip is provided for the transmitter and the full system, proving the feasibility of a digital future in radar.